The Symbolic Cremation of Agricultural Pests: Traditional Ecological Knowledge for Sustainable Agriculture in the Subak System of Bali - Pande Wayan Renawati; Eny Dyah Yuniwati; Mhd. Rafi’i Ma’arif Tarigan (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The symbolic cremation ritual for agricultural pests (Mrateka Sarwa Marana), constitutes an important component of Bali’s Subak system for sustaining agriculture through indigenous knowledge and collective ritual practices. This study examines the ritual process and the Traditional Ecological Knowledge (TEK) embedded in the Mrateka Sarwa Marana ritual. Employing a qualitative religio-cultural ethnographic approach, the research was conducted in Bedha Village, Tabanan, Bali. Data were collected through participant observation, semi-structured interviews with key informants, and library research. The findings show that the Mrateka ritual functions as a collective mechanism integrating ritual purification, ethical pest management, symbolic cremation, and community participation to strengthen ecological balance and social cohesion within the Subak system. The tradition also preserves TEK through irrigation management, synchronized planting, environmental sanitation, intergenerational knowledge transmission, and the complementary use of modern agricultural technology. The study proposes an integrative framework demonstrating how ritual, traditional ecological knowledge (TEK), and the Subak institution collectively contribute to sustainable agriculture and the achievement of the Sustainable Development Goals (SDGs).